EFEKTIVITAS PEMBIAYAAN UMKM DAN FAKTOR YANG MEMPENGARUHI PERMINTAAN PEMBIAYAAN UMKM PADA LEMBAGA KEUANGAN FORMAL DI KECAMATAN PALOH KABUPATEN SAMBAS - B01110070, Ayut Wahyudi (Jurnal Pembangunan dan Pemerataan, 2015)
This study, entitled "Effectiveness of UMKM financing and Factors Affecting UMKM financing request formal financial institutions in the district ofPaloh, Sambas regency." "This study aims to determine how effective UMKMfinancing in the formal financial institutions in the District of Paloh Sambasregency. The method used in this study is qualitative by using primary data. Waysof primary data collection using questionnaires, interviews and observation.Furthermore, the data were tabulated and analyzed.  Based on the results of the study, it shows that the effectiveness of UMKMfinancing at a formal financial institution credit union (CU). Bonaventure forUMKM sector is said to be quite effective trade, 90,00 percent of respondentsstated that the process of financing the initial filing procedure is relatively easy,then the distribution of funding for 96,00 percent of respondents stated, it ismedium (appropriate) with what is proposed, and 90,00 percent of of respondentsstated that a large installments are classified medium according to the ability ofmembers. Of the impact of financing, 74,00 percent of respondents said that thetrading business that received additional working capital increased revenue gains   And of the six factors that influence the demand for highly influentialfinancing is the type trade100,00 percent, 84,00 percent that has long been amember of and collateral / assurance 88,00 percent. While the cost of the loan, theterm of the installment and education level did not influence the financing requestformal financial institutions Credit Union (CU) Bonaventura in District PalohSambas district.  Keywords: Effectiveness Financing, UMKM Sector Trade.